2017
DOI: 10.1038/s41598-017-13239-w
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte Ratio Plus Prognostic Nutritional Index Predicts the Outcomes of Patients with Unresectable Hepatocellular Carcinoma After Transarterial Chemoembolization

Abstract: For many malignancies, inflammation-based scores correlate with survival. The neutrophil-to-lymphocyte ratio (NLR) and prognostic nutritional index (PNI) are immunonutritional indices associated with postoperative outcomes in patients with hepatocellular carcinoma (HCC). We evaluated whether a combined preoperative NLR and PNI score was prognostically superior to either index alone in 793 patients with unresectable HCC after transarterial chemoembolization. Patient demographic, clinical, and pathological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…All TACE procedures were performed by two operators using the same angiographic system (Allura Xper FD20, Philips Healthcare), which has been previously described [ 12 ]. Briefly, treatment with TACE was performed with a standard protocol under local anesthesia by 5-fluorouracil (800–1000 mg) and epirubicin-adriamycin (30–40 mg) followed with lipiodol (Lipiodol Ultra-Fluide; Andre Guerbet Laboratories, France) and polyvinyl alcohol foam embolization particles (100–500 μm in diameter; Cook, Bloomington, IN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…All TACE procedures were performed by two operators using the same angiographic system (Allura Xper FD20, Philips Healthcare), which has been previously described [ 12 ]. Briefly, treatment with TACE was performed with a standard protocol under local anesthesia by 5-fluorouracil (800–1000 mg) and epirubicin-adriamycin (30–40 mg) followed with lipiodol (Lipiodol Ultra-Fluide; Andre Guerbet Laboratories, France) and polyvinyl alcohol foam embolization particles (100–500 μm in diameter; Cook, Bloomington, IN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Published data revealed that these low cost inflammation-based markers including the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and prognostic nutritional index (PNI) are associated with prognostic significance in patients with HCC 10 13 . The elevated NLR was correlated with worse prognosis in HCC patients treated by RFA 13 , surgical resection 14 , transplantation 15 , and transcatheter arterial chemoembolization (TACE) 16 . A combination of the NLR and the PLR is a useful predictor for recurrence and prognosis in patients with HCC post RFA 17 .Another marker is the PNI, a combination of the serum albumin concentration and total lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2017) [26] who was the first one evaluated the ability of the combined NLR-PNI score to predict the outcomes of patients with early stage HCC after RFA and reported that after dividing their patients into three groups according to NLR-PNI scores, those patients with high combined scores had progressively worse outcomes relative to those with lower scores, and these differences were largely significant.…”
Section: Discussionmentioning
confidence: 99%